2004
DOI: 10.1387/ijdb.041874th
|View full text |Cite
|
Sign up to set email alerts
|

Blind cavefish and heat shock protein chaperones: a novel role for hsp90alpha in lens apoptosis

Abstract: Lens apoptosis plays a central role in cavefish eye degeneration. Heat shock proteins (hsps) can regulate apoptosis; therefore, we examined the relationship between constitutive hsp70 and hsp90 expression and lens apoptosis. The model system is Astyanax mexicanus, a teleost species consisting of an eyed surface-dwelling (surface fish) form and numerous blind cavedwelling (cavefish) forms. Optic primordia are formed in the cavefish embryo but they subsequently undergo lens apoptosis, arrest in development and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 40 publications
(51 reference statements)
8
53
1
Order By: Relevance
“…4, A and C-E), Hooven et al (42) reported that radicicol induced apoptosis by inhibiting the activity of Hsp90␤ in epidermal cells of cavefish. Plausible explanations for the variation in the effect of radicicol on cell viability could be the difference in cell type used (i.e., epidermal cell vs immune cells) or concentrations of radicicol.…”
Section: Discussionmentioning
confidence: 99%
“…4, A and C-E), Hooven et al (42) reported that radicicol induced apoptosis by inhibiting the activity of Hsp90␤ in epidermal cells of cavefish. Plausible explanations for the variation in the effect of radicicol on cell viability could be the difference in cell type used (i.e., epidermal cell vs immune cells) or concentrations of radicicol.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the degenerating CF lens epithelium proliferates normally, and lens degeneration seems to be due exclusively to apoptosis of fiber cells. Recent data suggest that the heat shock protein chaperone hsp90␣ has a role in this process, although it remains unclear how lens apoptosis is initiated by this molecule (Hooven et al, 2004).…”
Section: Proliferation and Apoptosis Patternsmentioning
confidence: 99%
“…Many of the regressive changes in the cavefi sh eye appear to be related to abnormalities of the lens. Cavefi sh lens fi ber cells do not terminally differentiate, instead they activate the hsp90 ␣ gene and initiate apoptosis [Jeffery and Martasian, 1998;Yamamoto and Jeffery, 2000;Hooven et al, 2004]. Subsequently, the Pax6 gene is downregulated in the corneal epithelium, the anterior eye sector does not differentiate, and retinal growth and photoreceptor cell differentiation are arrested [Yamamoto and Jeffery, 2000], although new cells are still produced in the ciliary marginal zone [Strickler et al, 2002].…”
Section: Introductionmentioning
confidence: 99%